PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHAREUNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDS AISYIYAH BENGKALIS - Alfisah '; Lazim. N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the low learning achievement of grade five science. Detailed criteria Minimum Value (KKM) IPA sets of 70. Among school students is 22, only 8 people (36.36%), which reached the KKM, while 14 (63.64%) who have not reached the KKM, with the average value average 63.86. This research is a classroom action research (CAR) by implementing cooperative learning model Think Pair Share (TPS). data collection instruments is the teacher, student activity sheets, and learning outcomes. Activities of teachers at the first meeting of the cycle I get a percentage of 58.33% enough category, at the second meeting of the first cycle increased with the percentage of 62.50% both categories., the first meeting of the second cycle of the teacher's activitie increase the percentage of 75.00% into either category and at the second meeting increased again with a percentage of 95.83% is very good category. Student activities at the first meeting of the first cycle of obtaining a sufficient percentage of the category of 54.16%, in the second meeting of the first cycle increased percentage of 62.50% to the good category, at the first meeting of the second cycle increased with the percentage of 70.83% both categories. At the second meeting increased with the percentage of 95.83% is very good category. From the results of the study before action Average 63.86 increase to 67.72 in Cycle I. In the second cycle increased to 73.86. Classical completeness in the first cycle and the second cycle has been reached.. Keywords: Model Cooperative Learning Think Pair Share (TPS), Natural Science Learning Outcomes